Andragogy and Financial Literacy in Indonesia: A Systematic Review of Adult Education Practices - Illa Susanti; Mustofa Kamil; Uyu Wahyudin; Iip Saripah (Journal of Nonformal Education, 2026)
Background: Financial literacy is increasingly recognized as a critical life skill that enables individuals to make informed decisions, manage resources effectively, and achieve long-term financial well-being. In Indonesia, financial literacy remains below global averages, with persistent gaps in inclusion and access. Adult learners, who face distinct socioeconomic and cultural challenges, require education that is responsive to their needs. Objective: This study reviews and synthesizes existing research on andragogy-based financial education for adults in Indonesia. The purpose is to evaluate how adult learning principles have been applied, to identify effective practices, highlight challenges, and map knowledge gaps for future research and policy development. Methods: A literature synthesis approach was employed, drawing on peer-reviewed journal articles, research reports, and academic books. Sources were selected based on relevance, quality, and applicability to the Indonesian context. The analysis involved critical synthesis of findings across studies, rather than a full systematic review, to identify patterns, contrasts, and gaps. Results: The review found that experiential learning, participatory approaches, and culturally contextualized methods—particularly those integrating Islamic financial principles—are most effective in improving adult financial literacy. Community-based programs show strong potential but face challenges, including limited adaptation to digital platforms, uneven trainer capacity, and weak policy alignment. Novelty: This study provides the first integrated synthesis that explicitly links andragogical principles with financial literacy initiatives in Indonesia. It uniquely incorporates Islamic financial literacy and digital finance perspectives, offering a context-specific contribution that bridges global theory with local practices. Conclusion: The review highlights the importance of andragogical approaches in strengthening adult financial literacy in Indonesia. It contributes theoretical insights and practical guidance for policymakers, educators, and practitioners to design more effective financial education strategies.